Utilization of banana peel flour as fibre ingredient in the waffle cones - Mohd Dom, Zanariah; Mohd Halimi, Nur Zaleqha; Mujianto, Lisnurjannah (Malaysian Society of Agricultural Engineers, 2019)
Banana fruits are the most eatable fruits in Malaysia. However, its beneficial skin mostly will be thrown away. The fibrous peels have slightly bitter taste with its good nutritional food attraction. They rich in starch and non-starch polysaccharides including food fiber, antioxidants, polyphenols, essential minerals such as potassium, provitamin A, carotenoids, B1, B2 and C that are acts as dietary roles in human health. In this study, Saba banana peel flour (BPF) sifted to 0.012 inch will convert into waffle cones. Preliminary study on the protein, moisture, crude fiber and fat were carried out for first stages of maturity. First stage BPF acts as water binding agent in food due to its high water holding capacity and have low oil holding capacity. BPF’s pH (6.15-6.46) is in standard wheat flour acidity range. Then, the BPF was substituted for 5%, 10%, and 20% of the wheat flour in a batter mix to make waffle cones. The substitution of BPF will affect the physicochemical properties by the pH, colour, odour and tensile strength. As the results, waffle cones of BPF had lower value of L* and b* which turned darker than controlled sample. The odour of banana smells in this waffle cones are sweet and fresh but only acceptable physical analysis for 5% and 10% substitution BPF. While for 20% substitution of BPF gave poor result in tensile strength and the sensory analysis but there also can be utilise for making dietary cookies.